Elastic, conductivity and dielectric properties of sodium lead germanate glass and optical interaction mechanism studies of erbium doped at germanate anomaly region / Mohd Fauzi Maulud - Maulud, Mohd Fauzi (2022)
A phenomenon known as germanate anomaly has drawn much attention due to the unique characteristic of germanate glass which can cause anomalous behavior in the physical properties of the glass. In this study, glasses with composition xNa2O-(99−x)[80GeO2:20PbO]-1Er2O3 (x = 0, 5, 10, 15, 20 and 25 mol%) were prepared by meltquenching method to elucidate the elastic, optical, dielectric and optical interaction of erbium ions of the glass around the germanate anomaly region. Structural investigation of glass samples was carried out by X-ray diffraction (XRD) and Fourier transform infrared (FTIR) spectroscopy while optical properties by UV-VIS spectroscopy and elastic properties were studied by ultrasonic pulse-echo method.